"МОСКВА ГУРАВ ДАХЬ РОМ" ГЭСЭН УЛС ТӨРИЙН ҮЗЭЛ БАРИМТЛАЛЫН ТУХАЙД - Ж.Жаргал (Politology, 2023)
In this article author analyzed political concept "Moscow - the Third Rome". This doctrine emerged in XVI century.Filofeiwas ahegumen of the Yelizarov Monastery near Pskov in the 16th century. He is credited with authorship of the Third Rome prophecy. Details of which are very scarce. Known as the presumed author of the concept of «Moscow - the Third Rome», which sets out the thesis in his letters.